The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0131519
|View full text |Cite|
|
Sign up to set email alerts
|

Unravelling the Structural and Molecular Basis Responsible for the Anti-Biofilm Activity of Zosteric Acid

Abstract: The natural compound zosteric acid, or p-(sulfoxy)cinnamic acid (ZA), is proposed as an alternative biocide-free agent suitable for preventive or integrative anti-biofilm approaches. Despite its potential, the lack of information concerning the structural and molecular mechanism of action involved in its anti-biofilm activity has limited efforts to generate more potent anti-biofilm strategies. In this study a 43-member library of small molecules based on ZA scaffold diversity was designed and screened against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 49 publications
0
50
0
Order By: Relevance
“…5a,b) when they are free in solution, showing emission maxima at 395 and 443 nm for p-aminosalicylic acid (k exc 5 325 nm) and p-aminocinnamic acid (k exc 5 380 nm), respectively. 16 This property allowed us to evaluate the fluorescence of the solid surface of the functionalized polyethylene.…”
Section: Surface Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…5a,b) when they are free in solution, showing emission maxima at 395 and 443 nm for p-aminosalicylic acid (k exc 5 325 nm) and p-aminocinnamic acid (k exc 5 380 nm), respectively. 16 This property allowed us to evaluate the fluorescence of the solid surface of the functionalized polyethylene.…”
Section: Surface Analysesmentioning
confidence: 99%
“…Indeed, cells use ROS as a signal or cue to adapt to a changing environment. 46 Recently, it has been found that E. coli proteins targeted by ZA 16 and SA 23 are widespread with a high percentage of identity in a wide range of microorganisms, included several E. coli pathogenic stains and bacteria involved in serious disease. Thus, it is possible that LDPE-CA and LDPE-ZA could exert their activity also against other bacterial strains.…”
Section: Surface Analysesmentioning
confidence: 99%
See 3 more Smart Citations